1999
DOI: 10.1097/00006534-199901000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Accompanying Arteries of the Lesser Saphenous Vein and Sural Nerve: Anatomic Study and Its Clinical Applications

Abstract: The arteries adjacent to the lesser saphenous vein and sural nerve were investigated in 10 fresh cadavers that had been systemically injected with a lead oxide-gelatin mixture. The accompanying arteries were found to lie along the lesser saphenous vein and sural nerve and to nourish the skin through venocutaneous and neurocutaneous perforators. On the basis of the anatomy of these accompanying arteries, the lesser saphenous venoadipofascial (VAF) pedicled fasciocutaneous flap and the lesser saphenous-sural ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 25 publications
2
103
0
4
Order By: Relevance
“…A pele do retalho retirado desta região é nutrida pelas artérias que acompanham a veia safena menor 16 e pelas comunicações entre o plexo suprafascial e o subdérmico. Assim, no seu trajeto subfascial, a artéria sural superficial mediana emite ramos que nutrem o plexo suprafascial e, através deste, nutre indiretamente a pele devido à grande comunica-Vendramin et al…”
Section: Discussionunclassified
“…A pele do retalho retirado desta região é nutrida pelas artérias que acompanham a veia safena menor 16 e pelas comunicações entre o plexo suprafascial e o subdérmico. Assim, no seu trajeto subfascial, a artéria sural superficial mediana emite ramos que nutrem o plexo suprafascial e, através deste, nutre indiretamente a pele devido à grande comunica-Vendramin et al…”
Section: Discussionunclassified
“…These flaps also called neurofasciocutaneous flaps [11] . In 1999 Nakajima et al [12] notified the accompanying vessels of the lesser saphenous vein and sural nerve, and proposed the term of veno-fasciocutaneous flap and neurovenofasciocutaneous flap. In 2003 Chang et al [13,14] demonstrated in experimental studies that cutaneous large superficial veins in distally-based flaps played a negative role and suggested ligate these big cutaneous veins (great/lesser saphenous vein) to prevent flap ingress.…”
Section: Historic Perspectivementioning
confidence: 99%
“…The distally based superficial sural artery flap referred as "sural flap" has become a major tool for reconstruction of the distal leg, ankle, and foot as described by Haug M D et al 2008 3 and according to the study of Nakajima et al, 4 the accompanying artery of the sural nerve (the median superficial sural artery) had few perforators to the skin in the upper half of the leg. Most recent study by Ali Mojallal et al in Feb 2017 5 on the accompanying arteries of the sural nerve and the lesser saphenous vein were studied.…”
Section: Discussionmentioning
confidence: 99%